IMPLEMENTATION OF A PROJECT-BASED LEARNING STAGES IN UKRAINIAN LANGUAGE LESSONS FOR 5th-6th GRADE GYMNASIUM STUDENTS - Filonova, Nataliia Andriivna (Молодий дослідник, 2025)
This article analyzes the stages of implementing project-based learning in teaching Ukrainian to 5th-6th grade gymnasium students. Key stages covered include topic selection, planning, research, discussion, presentation, and reflection. The focus is on how each stage impacts students’ development of independent learning skills, critical thinking, and communicative competence, which are essential for successful language acquisition, especially in the face of educational challenges. Each stage’s contribution to building core competencies, engaging students actively in learning, addressing educational setbacks, and boosting motivation for studying Ukrainian is also examined. A review of recent studies highlights the effectiveness of project-based learning in developing complex skills, demonstrating that this approach promotes student involvement, enhances motivation, and fosters social integration.